2021
DOI: 10.1007/s12041-021-01262-w
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of human ACE2 and TMPRSS2 in determining host–pathogen interaction of COVID-19

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is at present an emerging global public health crisis. Angiotensin converting enzyme 2 (ACE2) and trans-membrane protease serine 2 (TMPRSS2) are the two major host factors that contribute to the virulence of SARS-CoV-2 and pathogenesis of coronavirus disease-19 (COVID-19). Transmission of SARS-CoV-2 from animal to human is considered a rare event that necessarily requires strong evolutionary adaptations. Till date no other human cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 125 publications
0
97
1
Order By: Relevance
“…Our research group identified lead A. Indica phytochemicals having potential to bind human host protein TMPRSS2 involved in Spike-protein entry into the cell ( Senapati et al., 2021 ). Matveeva et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group identified lead A. Indica phytochemicals having potential to bind human host protein TMPRSS2 involved in Spike-protein entry into the cell ( Senapati et al., 2021 ). Matveeva et al.…”
Section: Introductionmentioning
confidence: 99%
“…This review summarizes the recent discoveries in the interaction of SARS-CoV-2 with various host cellular components and the immune system. Among the various interactions, ACE2 and TMPRSS2 proteins have been recognized as the major host proteins that are exploited by the virus for its entry into the host cell [ 165 , 166 ]. Other host proteins such as BRD2 and BRD4 were shown to interact with viral envelope proteins, thereby disrupting the histone acetylation, resulting in the altered transcriptional regulation of host genes [ 90 , 167 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its entry into the host cells is mediated by transmembrane proteases, of which the transmembrane serine protease 2 (TMPRSS2) is the main one. Recent studies have identified several key amino-acidic residues for S-protein interactions with the human ACE2 receptor and the TMPRSS2 membrane protease to initiate infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since ACE2 and TMPRSS2 are co-expressed in a limited number of tissues, the high viral transmissibility and the tissue tropism suggest that SARS-CoV-2 may use other proteases for cellular entry [7]. In fact, several proteases have been found to be involved in the transmission or infection process, including furin (a membrane-bound protease expressed in different tissues, mainly in the lungs [6]), ADAM17 (short for a disintegrin and metalloprotease 17), and cathepsin L.…”
Section: Introductionmentioning
confidence: 99%